Aktivitas Analgesik Topikal Gel Ekstrak Etanol 70% Daun Mint (Mentha piperita) pada Mencit Putih (Mus musculus) dengan Metode Hot Plate - Sawu, Sirilus Deodatus; Wibowo, Wibowo; Irawan, Fransisca Elsia One (Jurnal Ilmiah Medicamento, 2025)
Pain is one of the most common health problems, affecting approximately one-third of the global population. Pain management is generally carried out through the administration of analgesic drugs, which are classified into two major groups: opioid and non-opioid analgesics. However, the use of these drugs is associated with adverse side effects and a risk of dependence. One potential alternative is the development of natural-based analgesics, such as mint (Mentha piperita) leaves. To date, there have been no studies evaluating the effectiveness of ethanol extract of mint leaves as a topical analgesic. This study aimed to assess the topical analgesic activity of ethanol extract of mint leaves formulated into a gel dosage form. Analgesic activity was evaluated using a hot plate-induced pain model in male white mice. Gels containing 5%, 10%, and 15% concentrations of the extract were tested and compared with a negative control (gel base) and a positive control (Voltaren® gel). Observations at 30 minutes post-application revealed that the mean latency times of the 10% and 15% extract groups, as well as the positive control group, were significantly different from the negative control group (p-value < 0.05). The difference in the percentage of maximal possible effect (%MPE) between the 10% and 15% extract groups was relatively small, suggesting that the 10% concentration was sufficient to produce an optimal analgesic effect. In conclusion, the 10% ethanol extract of mint leaves in gel form exhibited topical analgesic activity and holds potential for development as a topical analgesic gel formulation.